An Efficient Method for Phosphorylation of Alcohols: Preparation of Porphyrin-Derived Phosphates - Pisarek, Sabina; Bednarski, Hubert; Gryko, Dorota (Synlett, 2012)
An effective method for the phosphorylation of phenols and various alcohols including porphyrins bearing hydroxyl groups was developed. The reaction of 6,7-bis(3-hydroxypropyl)-1,3,5,8-tetramethyl-2,4-divinylporphyrin with dialkyl chlorophosphate in the presence of DABCO as both a catalyst and a proton scavenger gave the desired phosphate in 97% yield.
Keywords: phosphorylation; dialkyl chlorophosphate; porphyrin; protoporphyrin IX